Revision of the genus Pselaphomorphus Motschulsky, 1855 (Staphylinidae, Pselaphinae: Jubini). Corrections - Vásquez-Vélez, Laura M. (Zootaxa, 2016)
In my revision of the genus Pselaphomorphus Motschulsky, 1855 (Vásquez-Vélez 2016) the depository of the holotype of P. cayennensis Vásquez-Vélez, 2016 was not listed. As a result, the requirements of Article 16.4.2 of the International Code of Zoological Nomenclature (International Commission on Zoological Nomenclature 1999) have not been met, making the name unavailable. This note aims at correcting the earlier mistake: the holotype of P. cayennensis is deposited at the Museum of natural history (Muséum d’histoire naturelle), Geneva, Switzerland.